Application of the LUminometric Methylation Assay to ecological species: tissue quality requirements and a survey of DNA methylation levels in animals. (2nd April 2014) - Head, Jessica A.; Mittal, Krittika; Basu, Niladri
Abstract The LUminometric Methylation Assay (LUMA) measures global DNA methylation. LUMA depends on digestion of DNA with methyl‐sensitive and methyl‐insensitive restriction enzymes, followed by pyrosequencing. Until recently, LUMA has been principally used for biomedical research. Here, we use chickens as a model to investigate sample quality issues relating to LUMA and then apply the method to ecological species. First, we assessed the effect of tissue storage conditions on DNA methylation values. This is an important consideration for ecological species because samples are not always ideally preserved and LUMA is sensitive to poor DNA quality. We found that good quality LUMA data could be obtained from chicken liver and brain tissues stored at 21 °C for at least 2 and 12 h, respectively. Longer storage times introduced nonspecific peaks to pyrograms which were associated with reduced DNA methylation. Repeatedly, freezing and thawing the tissues did not affect LUMA data. Second, we measured DNA methylation in 12 species representing five animal classes: amphibians (African and Western clawed frog), reptiles (green anole lizard), fish (yellow perch, goldfish, lake trout), mammals (American mink, polar bear, short‐beaked common dolphin, Atlantic white‐sided dolphin) and birds (chicken, Japanese quail). We saw a pattern of high DNA methylation in fish (84–87%), and intermediate levels in mammals (68–72%) and birds (52–71%). This pattern corresponds well with previous measures of DNA methylation generated by HPLC. Our data represent the first CpG methylation values to be reported in several species and provide a basis for studying patterns of epigenetic inheritance in an ecological context.